2014
DOI: 10.1152/ajpgi.00210.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of autophagy ameliorates hepatocellular damage following ischemia-reperfusion injury in murine steatotic liver

Abstract: Ischemia-reperfusion injury (IRI) is a common clinical consequence of hepatic surgery, cardiogenic shock, and liver transplantation. A steatotic liver is particularly vulnerable to IRI, responding with extensive hepatocellular injury. Autophagy, a lysosomal pathway balancing cell survival and cell death, is engaged in IRI, although its role in IRI of a steatotic liver is unclear. The role of autophagy was investigated in high-fat diet (HFD)-fed mice exposed to IRI in vivo and in steatotic hepatocytes exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 59 publications
4
33
1
Order By: Relevance
“…Using established in vitro and in vivo models of steatosis; we have earlier demonstrated the susceptibility of a fatty liver to IRI with increased necrosis (5) and autophagy. (4) In the present study, we investigated changes in sinusoidal spaces and microcirculation in a steatotic liver following IRI. We show that, in a fatty liver, sinusoidal space was reduced by 60% compared to a normal liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using established in vitro and in vivo models of steatosis; we have earlier demonstrated the susceptibility of a fatty liver to IRI with increased necrosis (5) and autophagy. (4) In the present study, we investigated changes in sinusoidal spaces and microcirculation in a steatotic liver following IRI. We show that, in a fatty liver, sinusoidal space was reduced by 60% compared to a normal liver.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations are in conformity with our earlier findings that imposing IRI on HFD fed mice resulted in increased liver injury as evidenced by increase in serum ALT levels, autophagy, and necrosis, while imposing IRI on lean mice did not increase liver injury. (3, 4)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms by which hepatocytes undergo cell death in the fatty liver after IRI have not been sufficiently explored. We have shown that a fatty liver, compared with a lean liver, has increased necrosis, apoptosis, and autophagy after IRI, which is associated with progression to fibrosis, cirrhosis, and hepatocellular carcinoma. Several groups have shown that cluster of differentiation 4–positive (CD4 + ) cells are the main drivers of IRI in a lean state, but the role of lymphocytes in IRI of NAFLD is virtually unknown.…”
mentioning
confidence: 95%